Association of Longitudinal Changes in NT-proBNP With Changes in Left Atrial Volume and Function: MESA. (25th January 2021) - Varadarajan, Vinithra; Ambale-Venkatesh, Bharath; Hong, Seo Young; Habibi, Mohammadali; Ashikaga, Hiroshi; Wu, Colin O; Chen, Lin Y; Heckbert, Susan R; Bluemke, David A; Lima, Joao A C
Abstract: BACKGROUND: The mechanism of left atrial (LA) remodeling is poorly understood. The aim of this longitudinal study was to investigate whether changes in NT-proBNP levels relate to alterations of LA structure and function over time in a multiethnic population. METHODS: From the prospective cohort study, the Multi-Ethnic Study of Atherosclerosis, our analysis included 1, 838 participants who underwent cardiac magnetic resonance imaging at the baseline and 10-year examinations, had NT-proBNP levels available at both time points, and did not develop heart failure, myocardial infarction, and/or atrial fibrillation. Multivariable linear regression was used to analyze the association between NT-proBNP level (log-transformed) at the 2 time points and change in LA volumes, LA emptying fractions (total, active, and passive), and LA longitudinal strain. Log NT-proBNP was categorized into Low-Low ( N = 681), Low-High ( N = 238), High-Low ( N = 237), and High-High ( N = 682) based on the median value at both time points. RESULTS: With the Low-Low group as the reference group, the High-High group experienced a greater increase in LA maximum and minimum indexed volumes: 3.1 ml/m 2 (95% confidence interval 1.98, 4.20) and 2.7 ml/m 2 (1.89, 3.51), respectively. The High-High group also experienced a greater decrease in LA total, passive, active emptying fraction, and longitudinal strain: −3.3% (−4.46, −2.11), −0.9% (−1.80, −0.02), −4.2% (−5.55, −2.76), and −2.3% (−3.80, −0.72), respectively. The Low-High group had similar associations, but the effect sizes were not as high. CONCLUSIONS: Adverse LA remodeling over 10 years of follow-up strongly correlates with prolonged elevated levels of intracardiac stress, as assessed by NT-proBNP levels. Graphical Abstract: